Syrup production via enzymatic conversion of a byproduct (broken rice) from rice industry - Spinosa, Wilma Aparecida; Santos Júnior, Vitório dos; Galvan, Diego; Fiorio, Jhonatan Luiz; Gomez, Raul Jorge Herman Castro (Acta Scientiarum. Technology, 2016)
In a hydrothermal process for the gelatinization of the rice starch, it was studied the rate of hydration, temperature and time. An incomplete 33 factorial design was used to evaluate the effects of temperature, enzyme/substrate relation and liquefaction time, with dextrose equivalent (DE) as the response variable. The maximum value obtained was 14.69% DE at 89ÂºC, with 0.21% (w/w) of enzyme to substrate in 22 minutes. For saccharification, it was studied enzyme/substrate ratios (0.6, 2.4, 4.2 and 6.0% (w/w)) at 60ÂºC at a pH of 4.30, yielding 49.23, 69.65, 65.12 and 74.67% DE, respectively, after 72 hours. The syrup had a content of 12.78, 16.87, 15.96 and 17.87% of glucose (w/v), pH 2.60 - 2.71. The starch content converted into glucose after liquefaction was 61.80% and after saccharification ranged from 75.16 to 77.05% for the relation enzymes substrate tested. Â